A short review on DNA damage and repair effects in lip cancer - Sneh M. Toprani (Elsevier, 2021)
Increasing trend in oral cancer (0.6% per year) and its related mortality has been reported worldwide since 2010. The United States alone reports an increase of 57% within the past 10 years. This emphasizes the need not only for designing strategies of prevention and planning but also for an effective treatment regime for the various oral cancers. Cancers of the lips, tongue, cheeks, floor of the mouth, and hard palate have been primarily classified under the category of oral cancers. If left undiagnosed, these cancers can be life threatening. Amongst these, the most undesignated and understudied cancer type is the lip carcinoma, which is either categorized under oral cancer or/as well as skin cancer or head and neck cancer. However, lip cancer corresponds to 25–30% of all diagnosed oral cancers. Though the etiology of lip cancer is not yet fully understood, numerous risk factors involved in its development are now being studied. The cells in the lip region are continuously exposed to various DNA damaging agents from endogenous as well as exogenous sources. Flaws in DNA repair mechanisms involved in eliminating these damages may be linked to the origin of carcinogenesis. Accumulation of DNA damage and defect in repair mechanisms may play a role in lip carcinogenesis and progression. This literature review is an exhaustive compilation of the research work performed on the role of DNA damage and repair responses in lip carcinoma which will pave a path for researchers to identify predictive DNA repair biomarker/s for lip cancer, and its diagnosis, prevention, and treatment.